PENGARUH GAYA HIDUP DAN KELAS SOSIAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK WARDAH DI TOKO MATA KOSMETIK KABUPATEN SOLOK SELATAN - Henryanto Abaharis; Rahmad Gandhi; Romi Susanto (Jurnal Bina Bangsa Ekonomika, 2024)
The purpose of this research is to determine the influence of lifestyle variables and social class on the purchasing decisions of Wardah products at Mata Cosmetics Store in South Solok Regency. This research method employs quantitative methods. Data collection techniques involve distributing questionnaires to 89 respondents using probability sampling. Respondents' answers are processed using SPSS. The results of this study indicate that lifestyle and social class have an impact on purchasing decisions for Wardah products at Mata Cosmetics Store in South Solok Regency